Design and Analysis of Underwater Docking System. (2018) - Senthilnathan, N.; Manhas, Kuber Singh; Utkarsh; Bhattacharya, Shiddhant
Abstract: The last few decades has seen good advancement in the design and use of docking systems for several fields including space. The present work involves designing a docking system that can operate between two underwater vehicles. Submarines are chosen as test vehicles and the system is designed to transfer physical and material goods between two submarines. The vehicles considered for the analysis are of same type with hatches attached to its left and right surfaces. Structural and fluid flow analyses are carried out on the designed docking system to ensure its stability under the action of water pressure. The pressure and velocity of the ocean currents at a particular depth of 250m are considered for the analysis. The variation of stresses across the docking system is recorded and the maximum deformation is found to be negligible. The pressure distribution and velocity variations are also analyzed and the results are found to be satisfactory